Development and experimental testing of a compact thermal energy storage tank using paraffin targeting domestic hot water production needs. (1st October 2020) - Dogkas, George; Konstantaras, John; Koukou, Maria K.; Gr. Vrachopoulos, Michail; Pagkalos, Christos; Stathopoulos, Vassilis N.; Pandis, Pavlos K.; Lymperis, Kostas; Coelho, Luis; Rebola, Amandio
Highlights: Finned tubes HEs immersed in PCM meet the demands for domestic hot water production. Coupling a latent heat storage unit with solar or heat pump units is efficient. The examined storage unit can produce instantly more than 100 l of hot water. Fast charging duration of less than 2 hours is accomplished. Abstract: In this work, a thermal energy storage tank using Phase Change Materials (PCM) is experimentally investigated. It is part of a thermal storage technology based on solar collectors and efficient heat pumps for heating, cooling and Domestic Hot Water (DHW) production. It comprises a rectangular tank filled with PCM and a staggered finned heat exchanger (HE). The tank is designed for DHW production according to the EU Commission Regulation No 814/2013 requirements. Stored energy density and heat transfer rate during the melting and solidification stages are used to evaluate the adequacy of produced hot water amount and the storage efficiency of the tank. Two organic PCMs were tested, A53 and A58H, having nominal melting temperatures of 53 °C and 58 °C respectively. With the defined operating conditions, the tanks can be charged either by the sun or by a heat pump in less than 2 h, with a heat transfer rate above 5 kW for the first half of the storage capacity. During discharging, the system can produce instantly 106 lt of DHW with temperature above 40 °C. Experimental results confirmed the ability of the tank to meet the requirements of a DHW installation and to increase the efficiency of the coupled solar collector or geothermal heat pump.